Self-Expandable Metal Stents for Colorectal Cancer: From Guidelines to Clinical Practice - Maria Pia Costa Santos; Carolina Palmela; Rosa Ferreira; Elídio Barjas; António Alberto Santos; Rui Maio; Marília Cravo (GE: Portuguese Journal of Gastroenterology, 2016)
Introduction: Colonic self-expandable metal stent placement is widely used for palliation of obstructive colorectal cancer. The European recommendations for stent placement as a bridge to elective surgery in obstructive colorectal cancer were recently reviewed. The aim of this study was to evaluate the efficacy and safety of stent placement in obstructive colorectal cancer and to discuss these recent guidelines. Materials and methods: Demographic characteristics, procedure indications, complications and final outcome in patients with obstructive colorectal cancer who underwent endoscopic stent placement between January 2012 and June 2015 were retrospectively analyzed. Statistical analysis was performed with SPSS V22. Results: Thirty-six patients were included, 20 (56%) women, mean age 70.6 ± 10.9 years. Stent placement as a bridge to elective surgery was performed in 75% (n = 27) of patients and with palliation intent in 25% (n = 9). In 94% (n = 34) of procedures, technical and clinical success was achieved. A total of eleven (11%) complications were observed: 2 migrations and 9 perforations. No procedure related death was recorded. When stents were placed as a bridge to surgery, average time between endoscopic procedure and surgery was 11.7 ± 9.4 days (excluding three patients who underwent neoadjuvant chemotherapy). Six perforations were recorded in this group: one overt and five silent (three during surgery and two after histopathological examination of the resected specimen). Twenty-one patients underwent adjuvant chemotherapy. During the follow-up period of 14.7 ± 10.9 months recurrence was observed in five patients. None of the recurrence occurred in the group of patients with perforation. Conclusions: In this study, stent placement was an effective procedure in obstructive colorectal cancer. It was mainly used as a bridge to elective surgery. However, a significant rate of silent perforation was observed, which may compromise the oncological outcome of these potentially curable patients. Prospective real life studies are warranted for a better definition of actual recommendations.